SUPERVISI PENDIDIKAN DI SEKOLAH ALAM BOGOR - Nita Karmila; Yudhie Suchyadi (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2020)
EDUCATION SUPERVISION IN NATURAL SCHOOL BOGORThis research is an interactive qualitative study with a descriptive approach that aims to explore in depth information about the implementation of educational supervision in the Natural School Bogor. Data obtained through observation, in-depth interviews and documentation studies. The results showed that the Natural School Bogor had carried out educational supervision on three main objects namely the curriculum, Human Resources (HR) and facilities and infrastructure. Based on field data, there are obstacles in the implementation of curriculum supervision. While supervision in the field of Human Resources and infrastructure can run well.